PEMBERDAYAAN MASYARAKAT DESA DI DESA SIBEROBAH KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Febrianza, Maliki Dhuha; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Community Empowerment in Siberobah Village, Gunung Toar District, Kuantan Singingi Regency in 2021 is an element of community development in the economic and political fields that is centered on the people. The aim of the research is to describe community empowerment in Siberobah Village and to identify the supporting and inhibiting factors for the community empowerment program in Siberobah Village. This type of research is qualitative. The type of research data used in this research is primary data in the form of data and information originating from primary sources and research informants, and secondary data in the form of documents obtained from related documents. The research location is Siberobah Village. Forms of village community empowerment activities can be in the form of providing goods, agricultural seeds/seeds, fisheries, plantations and trade because the Siberobah Village community has rich potential in natural resources, especially in the plantation sector. The result of this research is that there is an Empowerment program for the Siberobah village community using a fairly large village budget in its implementation. However, there is still a lack of knowledge among the Siberobah village community regarding how to properly plant and care for oil palms and a lack of role for the village government in evaluating village farmer groups. This is indicated by the absence of supervisors who assess the activities of the Siberobah village farmer group which will be an obstacle to reach the community empowerment. Keywords: Community Empowerment, Program, Palm Oil Seed Assistance